Prevalence of Worry-Induced Sleep Disturbance and Associated Factors among a National Sample of In-School Adolescents in Lebanon - Pengpid, Supa (Behav Sci (Basel), 2020)
Persistent worry can cause significant distress among adolescents. The goal of this study was to estimate the prevalence and correlates of worry-induced sleep disturbance (WISD) among adolescent school children in Lebanon. Cross-sectional, nationally representative data were analysed from 5849 adolescents (15 years median age) that took part in the “2017 Lebanon Global School-Based Student Health Survey (GSHS)”. The results indicate that the prevalence of WISD was 14.7%, 9.6% among males and 17.2% among females. In adjusted logistic regression analysis, loneliness, older age, female sex, having no close friends, infrequent bullying victimization, parents disrespected privacy, current tobacco use, ever cannabis use, high leisure-time sedentary behaviour and having sustained multiple serious injuries (past year) were associated with WISD. In addition, in unadjusted analysis, mostly or always feeling hungry (or low economic status), school truancy, having been physically attacked, frequently being in physical fights (past year), low peer support, parental emotional neglect, parents never checking homework, ever drunk and frequent soft drink intake were positively, and infrequent fast food intake was negatively, associated with WISD. One in seven students reported WISD and several associated factors were identified, which can aid intervention strategies. Multi-level interventions are needed targeting psychosocial distress, social-environmental factors and health risk behaviours to prevent WISD in this adolescent school population.